Salidroside Attenuates Apoptosis in Ischemic Cardiomyocytes: a Mechanism Through a Mitochondria-Dependent Pathway - Han Zhong; Hong Xin; Li-Xin Wu; Yi-Zhun Zhu (Elsevier, 2010)
Abstract.: In the present study, we investigated cardioprotective effects of salidroside, isolated from Rhodiola rosea L, on oxygen-glucose deprivation (OGD)-induced cardiomyocyte death and ischemic injury evoked by acute myocardial infarction (AMI) in rats. Pretreatment with salidroside notably ameliorated cell viability losses in a dose-dependant manner and in parallel it alleviated morphologic injury detected by electron microscopy. Mechanistically, diminished OGD-induced cardiomyocyte apoptosis was shown in salidroside-pretreated cardiomyocytes, in accordance with minimal reactive oxygen species (ROS) burst. Moreover, salidroside markedly upregulated the Bcl-2/Bax ratio and preserved mitochondrial transmembrane potential (ΔΨm). Salidroside administration also inhibited myocardial apoptosis in AMI rats by increasing phosphorylation of Akt and decreasing activation of caspase-3. These findings suggest that salidroside reduced ischemia-mediated myocardial damage. Salidroside therefore has potential to be a promising drug for preventing and treating myocardial ischemic diseases. Keywords:: salidroside, ischemia, cardiomyocyte, apoptosis, reactive oxygen species